The Effectiveness of Reducing Ammonia Content Using Phytoremediation Methods in Domestic Waste of Pelita Bangsa University - Nisa Nurhidayanti; Nadya Ulfani Sara (Universitas Diponegoro, 2021)
Pelita Bangsa University is a private university with an increasing number of students every academic year. The increase in the number of students causes an increase in the amount of domestic waste generated. This study aims to determine the effectiveness of reducing Ammonia content in Pelita Bangsa University Domestic Waste by phytoremediation method using Apu Wood (Pistia stratiotes L.) and Kana Flower (Canna Indica) as well as the use of coffee grounds as activated carbon. The first step in this research is the manufacture of activated carbon from coffee grounds. The next step is to take samples of the Pelita Bangsa University domestic waste test. The test samples were brought to the laboratory, and the Ammonia parameter was tested to determine the initial concentration of the waste. Then the next step is the acclimatization process of plants and then continued with the Range Finding Test process. After that, the waste treatment process is carried out with a phytoreactor. Furthermore, the waste from the phytoreactor processing is taken to the laboratory for testing the ammonia parameters. The last step is to analyze the test results data. Based on the results of laboratory tests, the ammonia content after the phytoremediation process with and without a filter is <0.1 mg/L with the effectiveness of reducing the ammonia concentration by 97.10% with the addition of coffee grounds activated carbon filter and 96.7% for the use of the phytoremediation method without filters.